Faculty Perceptions of Artificial Intelligence's Role in Enhancing Academic Performance: Field Study at Sebha University, Libya (Sirte University Journal of Humanities, 2025)
This study explores the faculty member's perspective towards the influence of AI on academic productivity in the context of Sebha University, Libya in terms of teaching, research and service activities. This cross-sectional study employed a descriptive-analytical method and data were gathered from 240 faculty members through a validated questionnaire. The study fills a gap in knowledge on AI readiness in resource-constrained higher education settings. Positive faculty attitudes about the integration of AI into the curriculum are reported in most subject areas. Findings: Gender and academic degree were found to have no significant effect, and evidence indicated that years of experience significantly (p ≤ 0.05) affected faculty attitudes. The results suggest a baseline acceptance and preparedness among the faculty, providing strategic opportunities for administrative leadership. The research suggests building up an overall regime covering technology boosting, targeted training and clear regulation policies for AI implementation. These findings will inform policy makers in navigating digital transformation in Libyan and other similar development contexts and highlight the significance of faculty perceptions in successful technology adoption strategies.
Keywords: Artificial Intelligence; Academic Performance; Higher Education; Faculty Perceptions; Sebha University; Libya